Sufentanil Combined with Nalbuphine via Patient-Controlled Intravenous Analgesia After Cesarean Section: A Retrospective Evaluation - Wang L; Wang Y; Ma Y; Mu X; Zhang Z; Wang H; Zheng Z; Nie H (Dove Medical Press, 2022)
Lini Wang,* Yiting Wang,* Yumei Ma, Xiaoxiao Mu, Zhen Zhang, Huan Wang, Ziyu Zheng, Huang Nie Department of Anesthesiology and Perioperative Medicine, Xijing Hospital, Fourth Military Medical University, Xi'an, People's Republic of China*These authors contributed equally to this workCorrespondence: Huang Nie, Department of Anesthesiology and Perioperative Medicine, Xijing Hospital, Fourth Military Medical University, Changle West Road 127, Xi'an, Shaanxi, 710032, People's Republic of China, Email niehuang@163.comPurpose: This retrospective study evaluated the efficacy, opioid consumption, and safety profile of two patient-controlled intravenous analgesia (PCIA) regimens (sufentanil combined with nalbuphine vs sufentanil alone) after cesarean section (CS).Patients and Methods: Parturients (n = 1808) received sufentanil combined with nalbuphine (SN group) or sufentanil alone (S group) as PCIA after CS. The primary outcome was the numeric rating scale (NRS) pain score with movement (NRS-M) at 24 h after CS. Secondary outcomes were NRS scores at rest (NRS-R) at 24 and 48 h after CS, NRS-M at 48 h after CS, cumulative PCIA bolus times, and opioid consumption during the first 24 and 48 h postoperatively, which was measured in morphine-equivalent doses.Results: The population comprised 993 and 815 subjects in the SN and S groups, respectively. At 24 and 48 h after CS, the respective NRS-M scores of the SN group (4.62, 3.37) were each significantly lower than those of the S group (5.18, 4.01; P < 0.01 for both). The corresponding NRS-S scores were similarly lower in the SN group (0.96, 0.19) than in the S group (2.05, 0.92; P < 0.01 for both). After adjusting for covariates, the SN group still had lower NRS-M than the S group at 24 h after CS (estimate adjusted = 0.565, P < 0.001). The PCIA bolus times were significantly lower in the SN group than in the S group. The rates of bradycardia and respiratory depression were lower in the SN group than in the S group. However, the rates of dizziness and postoperative hypotension were slightly higher in the SN group, and those of nausea/vomiting were comparable.Conclusion: Compared with sufentanil alone, sufentanil combined with nalbuphine for PCIA provided superior analgesia in parturient women after CS.Keywords: nalbuphine, sufentanil, patient-controlled intravenous analgesia, cesarean section